2011
DOI: 10.1007/s00299-011-1189-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of MdSOS2 reveals its involvement in salt tolerance in apple callus and Arabidopsis

Abstract: Plants respond to various environmental stresses by activating "stress genes". CIPKs (CBL-interacting protein kinases) family genes play an important role in the process of stress response. In this study, a CIPK gene MdSOS2 was isolated from apple (Malus × Domestica). Sequence alignment and phylogenetic analysis showed that it is highly similar with Arabidopsis AtSOS2 and contained the conserved domains and motifs. Expression analysis demonstrated that MdSOS2 expressed in all tested organs at different levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 43 publications
2
21
0
2
Order By: Relevance
“…Plant CIPK genes could be induced by different stresses, such as drought2344, salt45, and cold18. Various functional studies of plant CIPK genes provided clear evidence for their implication in stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Plant CIPK genes could be induced by different stresses, such as drought2344, salt45, and cold18. Various functional studies of plant CIPK genes provided clear evidence for their implication in stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated the functional conservation of the CBL-CIPK pathway in Populus (Yu et al, 2007), grape (Weinl and Kudla, 2009), sorghum (Li et al, 2010), and maize (Chen et al, 2011). Enhanced tolerance to diverse stresses has also been regularly observed in transgenic Arabidopsis because of the overexpression of CIPKs (Zhao et al, 2009;Chen et al, 2012), rice (Xiang et al, 2007), tomato Huertas et al, 2012), tobacco (Tripathi et al, 2009), and apple (Hu et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, the SOS pathway, in response to salinity stress, is also functionally conserved in plants (Martinez-Atienza et al, 2007; Tang et al, 2010). Moreover, some CIPK genes in Rosaceae species function similarly to AtCIPK24 / AtSOS2 in salt tolerance (Hu et al, 2012; Wang R.K. et al, 2012). …”
Section: Introductionmentioning
confidence: 99%